Penerapan Penempatan dan Penentuan Kapasitas Kapasitor Pada Jaringan Distribusi Tegangan Menengah Kota Medan Menggunakan Electrical Transient Analysis Program - Yoakim Simamora; Mega Silfia Dewy; Agnes Irene Silitonga; Muhammad Isnaini (ELECTRON Jurnal Ilmiah Teknik Elektro, 2023)
The characteristics of the electric power distribution system which is far from the generator and is generally radial in shape causes voltage drops. Voltage drops that are below tolerance cause a decrease in power quality on the consumer side of the distribution network. The methods used to improve voltage drops are network reconfiguration, distributed generator placement, and capacitor placement. In this study, placement capacitors were used to improve voltage profil in the Medan city medium voltage distribution network. Placement of capacitors and determination of capacitor capacity using Electrical transient analyzer program (ETAP). The initial condition of the medium voltage distribution network before the capacitor placement was carried out was an active power loss of 256.1 kW and a minimum voltage of 0,90 p.u. After placing the capacitors using the electrical transient analyzer program, it was obtained that the capacitors were placed on bus 18 and bus 34 with their respective capacitor capacities. 600 kVAR, after running the power flow, the power loss is 194.9 kW or reduced by 23.90% and the minimum voltage is 0,94 p.u or increased by 4.2%.